2011
DOI: 10.15388/na.16.2.14105
|View full text |Cite
|
Sign up to set email alerts
|

The Kaldor–Kalecki stochastic model of business cycle

Abstract: This paper is concerned with the deterministic and the stochastic delayed Kaldor–Kalecki nonlinear business cycle models of the income. They will take into consideration the investment demand in the form suggested by Rodano. The existence of the Hopf bifurcation is studied and the direction and the local stability of the Hopf bifurcation is also taken into consideration. For the stochastic model, the dynamics of the mean values and the square mean values of the model’s variables are set. Numerical examples are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…where (u, pu q ) corresponds to a fixed point (Y,K), and r is an adjustment cost. In our simulation, we use (p,q,r,u) = (0.3,0.2,1.0,3.0) [22]. To evaluate the system behavior under an income bias, weak signal, and noise, we consider b as the bias term ofẎ , a weak sinusoidal signal I ext (t) = Asin2πf S t, and a Gaussian white noise Dξ(t) (< ξ(t) >= 0,< ξ(t),ξ(t ′ ) >= δ tt ′ , < • > indicates average in t) for Eq.…”
Section: The Kaldor Business Cycle Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where (u, pu q ) corresponds to a fixed point (Y,K), and r is an adjustment cost. In our simulation, we use (p,q,r,u) = (0.3,0.2,1.0,3.0) [22]. To evaluate the system behavior under an income bias, weak signal, and noise, we consider b as the bias term ofẎ , a weak sinusoidal signal I ext (t) = Asin2πf S t, and a Gaussian white noise Dξ(t) (< ξ(t) >= 0,< ξ(t),ξ(t ′ ) >= δ tt ′ , < • > indicates average in t) for Eq.…”
Section: The Kaldor Business Cycle Modelmentioning
confidence: 99%
“…(These phenomena, which include coherence resonance, stochastic resonance, and noise-induced transitions, are called noiseinduced phenomena in this study.) Recent studies have examined the effects of additive noise on business cycles based on non-linear economic dynamic theory [21,22]. Especially, Bashkirtseva et al have shown that noise-induced transitions [17] arise in nonlinear economic dynamic models, such as the Kaldor business cycle model and the Goodwin business cycle model, with multiple attractors around the subcritical Hopf bifurcation [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies [2,3,4,6,8], the mechanisms for generating chaos in systems with asymptotically stable equilibria are provided. In contrast, in [54,55,56,60] unpredictability in the solutions of differential equations was considered a result of random perturbations with small probability. P.A.…”
Section: Introductionmentioning
confidence: 99%
“…Kaldor type macroeconomic models with shocks have been paid much attention by many authors as well. Mircea et al [18] studied the dynamics depicting the mean and variance of the system. The result suggests that the cyclic fluctuation is inherited by the mean and variance although perfect cyclic dynamics of the system has gone due to the shock.…”
mentioning
confidence: 99%